Yu-Gi-Oh! : 5D's. Volume 2, The D1 Grand Prix begins! - Hikokubo, Masahiro (Shonen Jump manga., 2012)
In New Domino City, the hottest game in town is the Turbo Duel. Fought from blazingly fast motorcycle called duel runners. On the outskirts of New Domino City, in a district known as Satellite, a new Turbo Duel hero emerges-- Ysei Fudo! On his custom-built Duel Runner. Ysei takes on all challengers. Fighting for his friends and the future of Satellite!